2013
DOI: 10.1186/1471-2164-14-380
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome based identification of mouse cumulus cell markers that predict the developmental competence of their enclosed antral oocytes

Abstract: BackgroundThe cumulus cells (CCs) enveloping antral and ovulated oocytes have been regarded as putative source of non-invasive markers of the oocyte developmental competence. A number of studies have indeed observed a correlation between CCs gene expression, embryo quality, and final pregnancy outcome. Here, we isolated CCs from antral mouse oocytes of known developmental incompetence (NSN-CCs) or competence (SN-CCs) and compared their transcriptomes with the aim of identifying distinct marker transcripts.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
(39 reference statements)
3
22
0
2
Order By: Relevance
“…The integration of biomolecular science, biophysics, and non-invasive analytical methods should vastly improve follicle culture systems, make easier the non-invasive assessment of oocyte nuclear and cytoplasmic development in cultured follicles, and lead to the identification of the molecular signature for oocyte competence. 73 …”
Section: Introductionmentioning
confidence: 99%
“…The integration of biomolecular science, biophysics, and non-invasive analytical methods should vastly improve follicle culture systems, make easier the non-invasive assessment of oocyte nuclear and cytoplasmic development in cultured follicles, and lead to the identification of the molecular signature for oocyte competence. 73 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used microarray analysis and real-time polymerase chain reaction (PCR) to focus on gene expression profiles in granulosa cells (GCs) or CCs in an effort to find potential biomarkers of oocyte quality (Assou et al 2006(Assou et al , 2010Patrizio et al 2007;Huang and Wells 2010;Assidi et al 2011;Vigone et al 2013). Using a non-invasive test to assess embryo potential on the basis of gene expression profiles of human CCs, Assou et al (2008) found that there was a correlation between the expression of some genes in CCs and embryo potential or pregnancy outcome, and proposed BCL2 L11, PCK1 and NFIB as biomarkers for predicting pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the use of integrative bioinformatics tools has recently provided new insights into the transcriptional and epigenomics programmes that act behind oocyte maturation and the process of folliculogenesis. Whole-genome transcriptional profiles are already available for human, mouse and cow oocytes (Adjaye, 2005;Huang andWells, 2010: Assou et al, 2011;Diedrichs et al, 2012;Labreque and Sirard, 2014) and cumulus cells (Assou et al, 2008;van Montfoort et al, 2008;Ouandaogo et al, 2011;Vigone et al, 2013;Fragouli et al, 2014;Xu et al, 2014). Also, the epigenetic signature (i.e., DNA methylation and histone acetylation and methylation) of the female gamete has been described either for specific genome sequences using the traditional bisulfite conversion and immunofluorescence assays (Endo et al, 2005;Yeo et al, 2005;Hou et al, 2008;Kageyama et al, 2007;Liu et al, 2004;Racedo et al, 2009;Zuccotti et al, 2011;Denomme et al, 2012;Qiao et al, 2010;Pan et al, 2012;De La Fuente et al, 2004;Akiyama et al, 2004;Spinaci et al, 2004) or, for the whole genome, employing the reduced representation bisulfite sequencing (RRBS), a technique that couples the classical bisulfite conversion with the next generation sequencing technology (Smallwood et al, 2011: Tomizawa et al, 2012.…”
Section: Discussionmentioning
confidence: 99%